Experiential methods in ethical education of nursing and midwifery students - Kosicka, Bogumiła; Ozdoba, Patrycja; Dziurka, Magdalena; Boczkowska, Sylwia; Machul, Michał; Chrzan-Rodak, Agnieszka; Dobrowolska, Beata (Nursing in the 21st Century, 2023)
EXPERIENTIAL METHODS IN ETHICAL EDUCATION OF NURSING AND MIDWIFERY STUDENTS Introduction. Nursing, midwifery ethics education has been changing over the years. The necessity to reduce the knowledge-practice gap has been highlighted, consequently, modern training methods - based on experience - have been introduced. Aim. To present the importance of empirical teaching methods in the formation of ethical competence of nursing and midwifery students and and the objectives of the project implemented under the ERASMUS + program, KA220-HED entitled “Strengthening the ethical competence of future nurses and midwives: An inter-professional action-learning project on experiential training methods (ETHCOM)”. Material and methods. A non-systematic literature review was performed using databases (PubMed, CINAHL Complete). The analysis included 38 articles published between 2010 and 2023 in Polish and English. Results. In traditional methods of ethical education, the teacher plays the main role, while in those based on experience – the student. Among the experiential methods of learning ethics by nursing and midwifery students that are effective in acquiring and development of ethical competence can be distinguished, e.g. learning through games, storytelling, simulation etc. The selection of an educational method in the process of training ethical competence among nursing and midwifery students is important so that future students are able to face contemporary ethical problems.